Dyslipidemic profile in Type 2 Diabetes Mellitus: A hospital-based study from Eastern Nepal - Das, Binod Kumar Lal; Prassan, Netra; Ansari, Mohammad Faiz; Agrawal, Kanishk; Tripathi, Saloni; Niraula, Apeksha (Journal of Biomedical Sciences, 2020)
Background: Dyslipidemia is highly prevalent in Type 2 Diabetes Mellitus (T2DM). It plays a major role in the pathogenesis for diabetic complications. This study intends to exemplify the pattern of dyslipidemia prevalent in T2DM patients attending tertiary care centre of Eastern Nepal. Material and methods: This is a hospital based cross-sectional study conducted in the T2DM patients visiting the routine biochemistry laboratory for their routine blood investigations. 226 patients were included who fulfilled the inclusion criteria. Biochemical parameters were analyzed in routine biochemistry laboratory in cobas c311 autoanalyzer. Results: Out of the 226 T2DM patients, 51% were female and 49% were male respectively. The mean age group was 54.15 ± 12.62 years. Mean value of, HbA1c level, total cholesterol, TG, HDL and LDL was 8.16 ± 2.59 %, 289.04 ± 47.83, 297.77 ± 119.64, 35.62 ± 12.64 140.88 ± 40.58 respectively. HbA1c was significantly correlated with the lipid profile in T2DM patients (p < 0.05). Conclusion: The findings from the present study depicts that the prevalence of dyslipidemia is higher in T2DM in our centre with hypertriglyceridemia being the major type of dyslipidemia in these patients. In addition, male exhibited higher rate of dyslipidemia compare to their female counterparts respectively.